Home-based pulmonary rehabilitation in people with bronchiectasis: a randomised controlled trial. Issue 2 (31st May 2021) - José, Anderson; Holland, Anne E.; Selman, Jessyca P.R.; de Camargo, Cristiane Oliveira; Fonseca, Diogo Simões; Athanazio, Rodrigo A.; Rached, Samia Z.; Cukier, Alberto; Stelmach, Rafael; Dal Corso, Simone
Aim: To investigate the short- and long-term effects of home-based pulmonary rehabilitation (HBPR) on functional capacity, quality of life, peripheral muscle strength, dyspnoea and daily physical activity in people with bronchiectasis. Methods: Randomised controlled trial with 63 participants with bronchiectasis. The HBPR group performed three sessions per week for 8 weeks (aerobic exercise: step training for 20 min; resistance training: exercises for quadriceps, hamstrings, deltoids and biceps brachii using elastic bands). The control group received a recommendation to walk at moderate intensity, three times per week. A weekly phone call was conducted for all participants, and the HBPR group received a home visit every 15 days. The primary outcome was distance in the incremental shuttle walk test (ISWT). Secondary outcomes were time in the endurance shuttle walk test (ESWT), number of steps in the incremental step test, quality of life, quadriceps muscle strength and daily physical activity. Measures were taken before and after intervention and 6 months later. Results: After the intervention, the HBPR group had increased ISWT distance compared with the control group with between-group difference 87.9 m (95% CI 32.4–143.5 m). In addition, between-group differences were found in the ESWT, incremental step test, quality of life and quadriceps muscle strength, favouring the HBPR group. After 6 months, no differences were observed between the groups. Conclusion: HBPR is an effective alternative offering of pulmonary rehabilitation for people with bronchiectasis. However, the programme was not effective in maintaining the benefits after 6 months of follow-up. Home-based pulmonary rehabilitation (HBPR) delivers improvements in functional capacity, peripheral muscle strength and QoL in people with bronchiectasis. HBPR is safe, well tolerated and can be considered an alternative rehabilitation programme. https://bit.ly/2Q2Bout